A qualitative systematic review of maternal infant feeding practices in transitioning from milk feeds to family foods. Issue 2 (3rd October 2016) - Harrison, Michelle; Brodribb, Wendy; Hepworth, Julie
Abstract: Evidence supports the establishment of healthy feeding practices early in life to promote lifelong healthy eating patterns protective against chronic disease such as obesity. Current early childhood obesity prevention interventions are built on extant understandings of how feeding practices relate to infant's cues of hunger and satiety. Further insights regarding factors that influence feeding behaviors in early life may improve program designs and outcomes. Four electronic databases were searched for peer‐reviewed qualitative studies published between 2000 to 2014 with transitional infant feeding practice rationale from developed countries. Reporting transparency and potential bias was assessed using the Consolidated Criteria for Reporting Qualitative Research quality checklist. Thematic synthesis of 23 manuscripts identified three themes (and six sub‐themes): Theme 1. Infant (physical cues and behavioural cues) focuses on the perceived signs of readiness to start solids and the feeding to influence growth and "health happiness." Theme 2. Mother (coping strategies and knowledge and skills) focuses on the early survival of the infant and the family and the feeding to satisfy hunger and influence infant contentment, and sleep. Theme 3. Community (pressure and inconsistent advice) highlights the importance of generational feeding and how conflicting feeding advice led many mothers to adopt valued familial or culturally established practices. Overall, mothers were pivotal to feeding decisions. Satisfying infant's needs to reach "good mothering" status as measured by societal expectations was highly valued but lacked consideration of nutrition, obesity, and long term health. Maternal interpretation of healthy infant feeding and successful parenting need attention when developing strategies to support new families.